Perbandingan Hasil Penggunaan Nail Gel Pada Kuku Asli dan Kuku Palsu Motif Leopard - FilaHasena; Puspitorini, Arita; Kusstianti, Nia; windayani, novia (Universitas Negeri Surabaya, 2021)
Nail art is the art of decorating nails so that one's appearance can look more presentable and beautiful by adjusting the condition of the client's nails. Nail art uses nail gel as a nail dye. This study aims to determine the comparison of the results of using nail gel applied to real nails and false nails with a leopard pattern. This research is a type of descriptive quantitative research. The purpose of this study was to determine the results of applying nail gel to natural nails and artificial nails and to compare the results between the two nails. Data collection was obtained through an online questionnaire distributed through social media facilities, namely Google forms to students of SMK Negeri 4 Banjarmasin, Skin & Hair Beauty Department. The data analysis technique uses the results of the percentage in terms of neatness, the result of greasing, in terms of beauty, suitability of motifs, and the results of the respondent's overall preference and the average result is calculated from the results of calculating these percentages. The results showed that (1) in terms of neatness of nail gel on natural nails scored 90.3% while false nails were 9.7% (2) In terms of applying nail gel on natural nails a score of 80.6% while fake nails 19.4 % (3) In terms of the suitability of nail gel motifs on natural nails, the score is 92.5% while fake nails are 7.5% (4) In terms of the beauty of nail gel on natural nails, the score is 91.4% while false nails are 8.6% ( 5) Overall preference for nail gel on real nails scored 92.5% while fake nails were 7.5%. From the score obtained when calculated using the average formula for nail gel on natural nails, it scores 89.46% and fake nails gets a score of 10.54%. Keywords: Nail art; nail gel; nails; fake nail